Effects of Continuous Blood Purification without Heparin on Strem-1, NSE, and IL-10 Levels In Patients With Sepsis: Blood Purification on Strem-1, NSE, and IL-10 Levels - Zeng, Yongping; Wu, Dansen; Zhuo, Xiuming; Song, JingShi (Cellular and Molecular Biology, 2022)
One of the most common causes of mortality and disability across the world is sepsis, a condition marked by an abnormal immunological reaction in the body. The prognosis of patients with sepsis is much improved when they are diagnosed early and provided with proper therapy. Soluble triggering receptors expressed on myeloid cells (STREM-1), Interleukin-10 (IL-10), neuronal serum enolase (NSE), and so on are possible biomarkers for the diagnosis of sepsis based on the pathophysiology. Blood purification treatment to control the cytokine storm induced by sepsis was regarded to be promising. Recently, the treatment of sepsis is likely to shift toward a multimodal approach. Hence in this paper, we investigated the effect of a continuous blood purification technique (hemofiltration without heparin followed by hemoadsorption) on STREM-1, NSE, and IL-10 levels in patients suffering from sepsis. A sample of hundred patients suffering from sepsis was randomly allocated to one of the two groups (study and control groups). The control group got standard sepsis care, whereas the research group got continuous blood purification treatment. To compare the differences between the two groups, we used t-statistical analysis. Blood STREM-1, IL-10, and NSE concentrations of the study group were significantly lesser than that of the control group after therapy. As a result, continuous blood purification can significantly minimize the dysregulated immune response in patients with sepsis, promote immune function and improve the survival rate.